PENGEMBANGAN PENYULUHAN URGENSI KESELAMATAN DAN KESEHATAN KERJA (K3) SERTA PELATIHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) BAGI PERSATUAN TUKANG MANDIRI - Samsul Bahri; Besperi Besperi; Lisa Martiah Nila Puspita (DHARMA RAFLESIA, 2018)
The most of navvies is the low level education informal worker. More than 80% of them have only completed their primary school. The navvies are lacking in Occupational Health and Safety (K3). They never wear Personal Protective Equipment (APD) in their activity. Half of them almost do not know about this standard and this equipment. While others say that it is impractical and interfere with their work while they wear it. The purpose of this program is providing information about the urgency of K3 and training in the use of APD for workers. The results of the application of science and technology show that the risk of navvy have the big potential accidents. The program created an awareness of few of them to apply K3 although not yet fully implemented. K3 is very important and useful for navvy. Keywords: safety, health, work, navvy, accidents